Pengembangan Sistem untuk Memonitoring Kondisi Fisiologi melalui Biometric (Suhu, Detak Jantung dan Kelembaban) Pengguna E-Learning berbasis Internet of Things (IoT) (Studi Kasus Coma) - Yudi Muliawan; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
E-learning is an alternative for the world of education where to increase the ease in the teaching and learning process, the aim is to determine the level of independence of students, success in understanding the material and the ability of students' communication techniques. Weak monitoring of student conditions and psychological factors are limitations in e-learning learning. The psychological side includes motivation, self-discipline and emotions, therefore it is necessary to develop a system to help monitor the condition of students in using e-learning. Data mining to see the physiological condition of students on the use of e-learning aims to determine school stress (source of stress from the educational environment) in a student. The development of the model used is the waterfall and object oriented (OO) approach. The system designed is able to display physiological conditions with parameters of body temperature, heart rate and also skin moisture. The system is implemented using the model view controller (MVC) concept with the help of the Laravel framework and the HTML, PHP and Javascript programming languages. The Internet of Things (IoT) devices used are ESP32, LM35 temperature sensor, pulse sensor, galvanic skin response (GSR) and use the Sukamoto fuzzy logic algorithm.